Carbohydrate hydrogel products do not improve performance or gastrointestinal distress during moderate-intensity endurance exercise - King, A. J.; Rowe, J. T.; Burke, L. M. (International Journal of Sport Nutrition and Exercise Metabolism, 2020)
The benefits of ingesting exogenous carbohydrate (CHO) during prolonged exercise performance are well established. A recent food technology innovation has seen sodium alginate and pectin included in solutions of multiple transportable CHO, to encapsulate them at pH levels found in the stomach. Marketing claims include enhanced gastric emptying and delivery of CHO to the muscle with less gastrointestinal distress, leading to better sports performance. Emerging literature around such claims was identified by searching electronic databases; inclusion criteria were randomized controlled trials investigating metabolic and/or exercise performance parameters during endurance exercise >1 hr, with CHO hydrogels versus traditional CHO fluids and/or noncaloric hydrogels. Limitations associated with the heterogeneity of exercise protocols and control comparisons are noted. To date, improvements in exercise performance/capacity have not been clearly demonstrated with ingestion of CHO hydrogels above traditional CHO fluids. Studies utilizing isotopic tracers demonstrate similar rates of exogenous CHO oxidation, and subjective ratings of gastrointestinal distress do not appear to be different. Overall, data do not support any metabolic or performance advantages to exogenous CHO delivery in hydrogel form over traditional CHO preparations; although, one study demonstrates a possible glycogen sparing effect. The authors note that the current literature has largely failed to investigate the conditions under which maximal CHO availability is needed; high-performance athletes undertaking prolonged events at high relative and absolute exercise intensities. Although investigations are needed to better target the testimonials provided about CHO hydrogels, current evidence suggests that they are similar in outcome and a benefit to traditional CHO sources.